Effects of sitagliptin on counter‐regulatory and incretin hormones during acute hypoglycaemia in patients with type 1 diabetes: a randomized double‐blind placebo‐controlled crossover study. Issue 6 (24th March 2015) - Schopman, J. E.; Hoekstra, J. B. L.; Frier, B. M.; Ackermans, M. T.; de Sonnaville, J. J. J.; Stades, A. M.; Zwertbroek, R.; Hartmann, B.; Holst, J. J.; Knop, F. K.; Holleman, F.
Abstract : Aims: To assess whether the dipeptidyl peptidase‐4 (DPP‐4) inhibitor sitagliptin affects glucagon and other counter‐regulatory hormone responses to hypoglycaemia in patients with type 1 diabetes. Methods: We conducted a single‐centre, randomized, double‐blind, placebo‐controlled, three‐period crossover study. We studied 16 male patients with type 1 diabetes aged 18–52 years, with a diabetes duration of 5–20 years and intact hypoglycaemia awareness. Participants received sitagliptin (100 mg/day) or placebo for 6 weeks and attended the hospital for three acute hypoglycaemia studies (at baseline, after sitagliptin treatment and after placebo). The primary outcome was differences between the three hypoglycaemia study days with respect to plasma glucagon responses from the initialization phase of the hypoglycaemia intervention to 40 min after onset of the autonomic reaction. Results: Sitagliptin treatment significantly increased active levels of glucose‐dependent insulinotropic polypeptide and glucagon‐like peptide‐1. No significant differences were observed for glucagon or adrenergic counter‐regulatory responses during the three hypoglycaemia studies. Growth hormone concentration at 40 min after occurrence of autonomic reaction was significantly lower after sitagliptin treatment [median (IQR) 23 (0.2–211.0) mEq/l] compared with placebo [median (IQR) 90 (8.8–180) mEq/l; p = 0.008]. Conclusions: Sitagliptin does not affect glucagon or adrenergic counter‐regulatory responses in patients with type 1 diabetes, but attenuates the growth hormone response during late hypoglycaemia.